Jumper technique preparatory phase excelling model for academic basketball - Marchenko, N. V.; Ilyin, A. A.; Kapilevich, L. V. (Theory and Practice of Physical Culture, 2018)
It is common knowledge that the preparatory phase in a jump shot (jumper) technique largely predetermines success of attacks in basketball due to the bodily elements being duly arranged as required by the relevant biomechanical movement regularities and bioelectrical activity patterns of the trunk and lower limb muscles. An educational experiment under the study was designed to rate benefits of the proposed jump shot preparatory technique excelling model. Subject to the study was Experimental Group (EG, n=12) and Reference Group (RG, n=12) composed of 18-20 year-old university students. The experiment was 6 months long (October through March), with 4 training sessions per week in both of the groups. The EG training system was designed to include special jumper preparatory phase excelling exercises to train jumpers with both feet facing the hoop. Every athlete was subject to pre- and post-experimental tests to rate their special fitness, jumping ability and ball control skills in the jump shot sequence. The special exercises to improve the jump shot preparatory technique with an emphasis on the feet position were found beneficial as verified by the notable progress of the EG versus RG in the jump shooting skills.